Plant Regeneration from Leaf-derived Callus in Ablemoschus esculentus (L.) Moench - Khalekuzzaman, M (Bangladesh Journal of Genetics and Biotechnology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Keywords: Abelmoschus esculentus; Callus induction; Shoot formation; Plantlet regeneration Bangladesh j. genet. biotechnol. 7 (1&2): 83-85, 2006 (June & December)